Digital Technologies in healthcare: promises and challenges - Korzh, Oleksii (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Digital technology holds promise and has the potential to revolutionize healthcare and drug development by changing the way we collect, process and visualize health data. The potential uses are diverse, have applications in many therapeutic areas, and are likely to develop rapidly. The ultimate goal should be a better understanding of disease variability, response to treatment, and lower health care costs and more efficient clinical research. In addition, the introduction of new ways of collecting data remotely can provide new treatments and care management for all patients in need. The challenges associated with the adoption of digital technologies are significant. The scientific community will benefit from frequent exchange of information to share results and lessons learned; this will facilitate the development and implementation of best practices for technology deployment, data collection, analysis and interpretation.